Water Decolorization Using UV Radiation and Hydrogen Peroxide: A Kinetic Study - Martin, Carlos Alberto (2001)
Sometimes, provision of water for domiciliary consumption faces the problem of natural contamination originated by the presence of organic substances such as humic or fulvic acids. Very often, after conventional sanitary treatments this water exhibits a persistent yellowish coloration that affects its use. Moreover, these substances may act as precursors of tri-halomethanes formation during pre-desinfection with chlorine. This paper presents, with a simplified mechanistic approach, the intrinsic reaction kinetics of natural water decolorization employing UV radiation and hydrogen peroxide. The main variables for the model are: contaminant concentration expressed as TOC, hydrogen peroxide concentration and the photon absorption rate.